Analisis Kemampuan Konservasi dan Seriasi pada Anak Usia 10 Tahun Berdasarkan Teori Operasional Konkret Jean Piaget - dani, fira afrian (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the conservation and seriation abilities of 10-year-old children based on Jean Piaget's concrete operational theory. Piaget's theory states that at the concrete operational stage (ages 7-11), children begin to think logically about tangible objects and understand the concepts of conservation and seriation. This research employs a qualitative descriptive method using observation and interview techniques with fourth-grade elementary school students. The findings indicate that most 10-year-old children have grasped the concepts of quantity, volume, and mass conservation, although some errors in application still occur. Meanwhile, their seriation skills develop well, particularly in ordering objects based on size and quantity. Experience and learning environments play a crucial role in the development of these abilities. In conclusion, the majority of 10-year-old children have reached the concrete operational stage in line with Piaget's theory, although individual variations in understanding conservation and seriation remain.